Pengaruh Literasi Kewirausahaan Lingkungan Keluarga dan Locus of Control terhadap Minat Berwirausaha pada Mahasiswa Universitas Mulawarman - Rostina Rostina; Muhammad Fikry Aransyah (STKIP PGRI SITUBONDO, 2023)
This research was conducted to analyze the effect of entrepreneurial literacy, family environment, and locus of control on interest in entrepreneurship in undergraduate students at Mulawarman University. This study used quantitative methods and 100 respondents to collect data using a questionnaire. The data analysis technique used is validity and reliability test, classic assumption test, multiple linear regression, t test and f test. The results showed that partially the entrepreneurial literacy variable had no significant effect on the interest in entrepreneurship, the family environment variables and locus of control had a significant effect on the interest in entrepreneurship. Simultaneously the variables of entrepreneurial literacy, family environment, and locus of control have a significant effect on interest in entrepreneurship in Mulawarman University students.